Le monologue intérieur — une technique de l’introspection - Désfalvi-Tóth, András (Verbum – Analecta Neolatina, 2006)
Stream of consciousness is themanifestation of verbality in writing. Through the narrative technique of stream of consciousness, the writer has the opportunity to use the a very personal tone. This study examines three short stories by Valery Larbaud, the French writer and translator, which are characterized by this unique symbiosis of verbality and orality. This narrative technique is mainly suitable for the depiction of feelings and thoughts and not the narration of events. Its striking structural feature is the incoherent composition of sentences. Larbaud attributed great significance to narration carried out with the technique of stream of consciousness. The heroes of the three Larbaud short stories, which are in the scope of this study, have emotional problems to solve. The main topic of their "audible thinking" is the problem of faithfulness and the spiritual and physical distances between man and woman. Journey through time and space often gives the impression of a film script: the narrator depicts past and imaginary future in incoherent structured sentences which resemble the form of snapshots.